2005
DOI: 10.1242/dev.01948
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of chondroitin sulfation balance by chondroitin-4-sulfotransferase 1 is required for chondrocyte development and growth factor signaling during cartilage morphogenesis

Abstract: Glycosaminoglycans (GAGs) such as heparan sulfate and chondroitin sulfate are polysaccharide chains that are attached to core proteins to form proteoglycans. The biosynthesis of GAGs is a multistep process that includes the attachment of sulfate groups to specific positions of the polysaccharide chains by sulfotransferases. Heparan-sulfate and heparan sulfate-sulfotransferases play important roles in growth factor signaling and animal development. However, the biological importance of chondroitin sulfation dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
171
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(178 citation statements)
references
References 51 publications
7
171
0
Order By: Relevance
“…24 Thus, senescence appears to be associated with both gain-of-function of HRAS and loss-of-function of C4ST-1, consistent with our model that loss of C4ST-1 function is important for phenotypic manifestation of oncogenic HRAS signaling. In addition to Costello syndrome, a group of multiple congenital anomaly syndromes collectively named RASopathies have been shown to be associated with germline mutations in various genes of the RAS/ MAPK pathway.…”
Section: C4st-1 In Costello Syndromesupporting
confidence: 87%
See 3 more Smart Citations
“…24 Thus, senescence appears to be associated with both gain-of-function of HRAS and loss-of-function of C4ST-1, consistent with our model that loss of C4ST-1 function is important for phenotypic manifestation of oncogenic HRAS signaling. In addition to Costello syndrome, a group of multiple congenital anomaly syndromes collectively named RASopathies have been shown to be associated with germline mutations in various genes of the RAS/ MAPK pathway.…”
Section: C4st-1 In Costello Syndromesupporting
confidence: 87%
“…The analysis of proliferation rates by BrdU incorporation was performed as previously described. 24 Western blot analysis was performed by separating cell lysates in TNTE-based lysis buffer on 10% SDS-PAGE gels, followed by transfer to nitrocellulose membranes and incubation with mouse a-C4ST-1 (Abcam, 1:100) and mouse a-beta-tubulin (Abcam, 1:1000) antibodies.…”
Section: Biochemical and Cell Biological Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…9 Recently, it has been reported that a broad spectrum of skeletal dysplasias result from mutations causing undersulfation of chondroitin sulfate chains in humans and in mice. [10][11][12][13][14] In contrast, no association between CSPGs and human peripheral neuropathies has been reported to date.…”
Section: Introductionmentioning
confidence: 99%